Sistema automático de aquisição de dados para ensaio triaxial - Lira, Emidio Neto de Souza (1988)
Microcomputer based data acquisition system are initially described. The use of these systems for geotechnical tests and the dificulties that may arise when implementing these systems are emphasised. The data acquisition system at the COPPE Geotechnical Laboratory is subsequently described. This system was used to log undrained triaxial tests, the results of these being presented in a report type format. The material tested was a soft clay of the Caju District close to Guanabara Bay and sampled under a failed sanitary fill. Test results are analised in the ligth of critical state soil mechanics theory. This is hoped to contribute to the back calculation of the sanitary fill failure.